Perceived safety and mental health among Asian American women: Exploring the moderating role of loneliness and resilience - Jiepin Cao; Sarah Shevrin; Linh M. An; Jennifer A. Wong; Sugy Choi; Stella S. Yi; Chau Trinh-Shevrin; Sahnah Lim (PLoS ONE, 2025)
Asian American women are an understudied population facing a substantial mental health burden, largely driven by the increasing rates of gender- and race-based violence and discrimination. Perceived safety, a key factor influencing mental health, has been underexplored. This study aimed to 1) examine the relationship between perceived safety with mental health outcomes (i.e., depression and anxiety); 2) examine the link between safety-related behavioral modifications and mental health outcomes; and 3) explore the moderating effects of loneliness and resilience on these relationships, drawing from a community sample of n = 345 Asian American women. Perceived safety was defined as feeling safe in public spaces, transportation and neighborhoods. In our study, 28.7%, 56.2% and 20.6% of women reported feeling unsafe in public spaces, transportation and neighborhoods, respectively. Feeling unsafe in public spaces was associated with higher odds of depression (aOR=2.37, 95%CI: 1.40, 4.02) and anxiety (aOR=2.61, 95%CI: 1.56, 4.37). Avoiding public spaces, leaving home or transportation were linked to increased odds of depression (aOR=2.05, 95%CI: 1.23, 3.40; aOR=2.26, 95%CI: 1.37, 3.74; aOR=2.03, 95%CI: 1.16, 3.57, respectively) while only avoiding leaving home was associated with anxiety (aOR=2.04, 95%CI: 1.24, 3.36). Loneliness moderated the association between avoiding public spaces and anxiety: avoiding public spaces was significantly associated with greater odds of anxiety among women who were not lonely (aOR = 4.77, 95% CI: 1.24–18.34), but not among those who were lonely (aOR = 0.93, 95% CI: 0.53–1.64). Resilience did not moderate these relationships (all p > .050). Our findings highlight the mental health impacts associated with reduced perceptions of safety and safety-related behavioral modifications in this group, highlighting the pervasive fear experienced by Asian American women in their day-to-day lives, and emphasizing the need for targeted interventions to address the unique safety challenges faced by Asian American women.